An Analysis of Learners’ Oral Errors: A Study in One-to-one EFL Classroom Interaction - Sitti Syakira; Murni Mahmud; Sahril Sahril (TLEMC (Teaching and Learning English in Multicultural Contexts), 2021)
Correcting the repeated errors produced by the learners is one of the most frustrating things to do by teachers. However, it is natural for the students to commit errors while learning since it can be a sign of improving language competence and as a facilitating factor in second language learning (Atmaca, 2016). This study aims to find out the types and frequency of learners’ oral error occurrence during the teaching and learning process in one-to-one EFL classroom interaction. This research applied descriptive qualitative research with case study design. Two adult learners, who had the same English proficiency level, were chosen as research participants through purposive sampling in Amsterdam Institute, an informal school applying tailor-made system in the teaching and learning process. The data were collected through observation during teaching and learning process, and analyzed based on data analysis procedures consisting of data reduction, data display, and conclusion drawing and verification. The results revealed that all types of errors proposed in this research appeared during the observation and data analysis. Grammatical error dominated the error type, and lexical error was the least error type produced by the learners. Unsolicited use of L1 is excluded from the discussion of the result finding since it is not a part of the error type studied (Lyster, 1998). Furthermore, another finding indicates that the error committed by the learners continuously appeared in the next meeting the researcher observed. Therefore, it is suggested that the teacher should provide more triggers as an attraction for the learners’ intention so that they can figure out more about their errors, and engage the learners to provide themselves self-correction or self-repair by prompting them.